Post-Bologna practices of teaching and learning: An experience of active learning in Research Methodology in Education - Monteiro, Sílvia (2021)
Trabalho apresentado em: "ECER 2021: Education and Society: expectations, prescriptions, reconciliations", Geneva (online).